Effect of the shape of an organic water–coal fuel particle on the condition and characteristics of its ignition in a hot air flow; Russian Journal of Physical Chemistry B; Vol. 10, iss. 6 - Glushkov D. O. Dmitry Olegovich; Zakharevich A. V. Arkadiy Vladimirovich; Strizhak P. A. Pavel Alexandrovich; Syrodoy S. V. Semen Vladimirovich (2016, 2016)
Title screen